General aspects related to central venous access: a surgical approach (Research, Society and Development, 2023)
The objective of this study is to analyze and describe the main concepts and contexts regarding the insertion of the central venous catheter, and as secondary objectives, to point out the main complications and indications for the procedure. Making this technique safer and valuing the prognosis of patients. Aiming at exposing scientific productions and reconstructing concepts and lines of thought, articulating knowledge from several renowned works, in an attempt to tread paths in the target direction of new conceptions and networks of thought. The present study is a narrative review of the research on central venous access and the introduction of the central venous catheter. A search for articles was carried out in the Medical Literature Analysis and Retrievel System Online (MEDLINE), Scientific Electronic Library Online (SciELO) and PubMed databases, with the following Health Sciences Descriptors (DeCS): Venous access; Central Venous Catheter; Surgery; Patient safety. Selecting articles between the periods of 2005 to 2022, in English, Portuguese and Spanish, to increase the level of relevance and quality of the review, in addition to the technical-scientific basis arising from literary works renowned by history. It boils down to an intravascular catheter with an end close to the cardiac extremities or great vessels, aorta, pulmonary artery, inferior and superior vena cava, internal jugular, femoral, brachycephalic and, especially in neonates, umbilical artery and vein. When it comes to medical indications, the practice of the procedure varies, such as: hemodynamic instability due to failure in the first access attempt, parenteral nutrition, osmotic medication, need for continuous infusion of medication.